PENGARUH UKURAN PERUSAHAAN, KEPEMILIKAN MANAJERIAL, PROFITABILITAS, DAN LEVERAGE TERHADAP PENGUNGKAPAN TANGGUNG JAWAB SOSIAL PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PERIODE 2013-2016 - Nova Novita Nurmalasari, 14.05.52.0016; Sunarto, Sunarto (Students' Journal of Accounting and Banking, 2018)
Many from various fields of the company began to run CSR. Because CSR programs can improve the company's image in the eyes of the community. The population in this study are manufacturing companies on the Indonesia Stock Exchange in 2013-2016. Conduct research using documentation from Indonesia Capital Market Directory (ICMD), Financial Reports and Annual Reports. Using purposive sampling technique with a total sample of 54 companies. Analysis tools that are multiple linear regression. The results of this study indicate that the firm size variable has a significant negative effect on CSR disclosure in the company's annual report. Leverage has a significant positive effect on CSR disclosures in the company's annual report. Managerial ownership variables and profitability, does not affect on CSR disclosure in the company's annual report. Keywords: Corporate Social Responsibility, Company Size, Managerial Ownership, Profitability, and Leverage